A EMPOWERMENT OF MOTHERS IN CARE OF CHILDREN WITH STUNTING IN PERCUT SEI TUAN VILLAGE: STUNTING - Triwibowo, Cecep Triwibowo; Lestari; Juliana (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Stunting events that have occurred since childhood are associated with slower motor development and lower intelligence levels (Martorell et al. 2010). Several studies show that children who experience stunting during their toddler years have low cognitive levels, poor learning and psychosocial achievement (Achadi 2012). The incidence of stunting in toddlers is one of the global nutritional problems. Based on UNICEF data from 2000-2007, it shows that the prevalence of stunting in the world reached 28%, in South Asia it was 38% and in eastern and southern Africa it was 40%. When compared with the "non-public health problem" limit according to WHO for stunting problems of 20%, almost all countries in the world experience public health problems. This is proven by the prevalence of stunting among children under five in developing countries of 30% (UNICEF Report 2009). The target for achieving this activity is toddlers who experience stunting in Percut Sei Tuan village, so that the community can know how to: 1) Mothers know the importance of nutrition during pregnancy, exclusive breastfeeding, MPASI and toddler growth and development. 2) Mother knows about stunting, how to overcome and prevent stunting. 3) Mothers know the nutritional needs of their toddlers. 4) Reducing the number of stunting in Percut Sei Tuan village. And 5) Increasing public knowledge regarding PHBS to prevent stunting. The outputs and achievement targets of the activities are as follows: 1) Scientific publications in journals. 2) IPR 3) Booklet 4) Increased understanding and skills of mothers and 5) Improved public health/education (general community partners). Implementation methodology: 1) Preparation Stage, 2) Implementation stage, 3) Providing Health Education Materials and 4) Monitoring and evaluation. As a result of community service, the majority of knowledge of mothers with stunted children before receiving counseling was less knowledgeable, as many as 9 respondents (50.0%) and the majority of health cadres' knowledge after receiving counseling with good knowledge was 10 respondents (55.6%). The outputs and targets that have been achieved from the activities are as follows: 1) Manuscript, 2) Booklet and 3) Leaflet.